Novel method to determine element concentrations in foliage of poplar and willow cuttings. Issue 9 (1st September 2016) - Evangelou, Michael W.H.; Bürgi, Annina; Robinson, Brett H.; Günthardt-Goerg, Madeleine S.; Schöngens, Marcel; Schulin, Rainer
ABSTRACT: Measuring the uptake of the chemical elements by plants usually requires the destructive harvest of the plants. Analyzing individual leaves is unsatisfactory because their elemental concentration depends on their age and position on the branch or stem. We aimed to find an easy method to determine the elemental concentrations using a few suitable single leaves along the main shoot of poplar ( Populus monviso ) and willow ( Salix viminalis ) cuttings at the end of the first season. Using Ca, Cd, Mn, Fe, K, P, Pb, and Zn concentrations, measured in selected leaves along the main shoots of the cuttings, mathematical functions were derived, which described best their distribution. Elemental allocation patterns were independent of the soil characteristics and soil element concentrations. Based on these functions, three leaves from specific positions along the main shoot were selected, which could accurately describe the derived functions. The deviation of the calculated average concentration, based on the 3-leaves method, was ≤15% in approximately 65% of the cases compared to the measured concentration. This method could be used to calculate element concentrations and fluxes in phytomanagement, biomonitoring, or biomass productions projects using one-season poplar or willow cuttings.